The The Relationship between Family Support and Maternal Attitude with Early Initiation of Breastfeeding in Infants Aged - Ramdana, Ramdana; Friscila, Ika; Anisa, Fadhiyah Noor (Fakultas Ilmu Kesehatan, 2024)
One of the other things that causes high IMR is giving MP ASI too early. The high provision of Complementary Food for Early Breastfeeding is influenced by family support. The internal factor that influences early complementary feeding is the mother's attitude. Tanjung Seloka Health Center, Kotabaru Regency, is the health center with the third lowest coverage of exclusive breastfeeding, namely 83.7%. The aim of this research is to determine the relationship between family support and mother's attitude with early complementary breastfeeding to infants aged <6 months in the work area of the Tanjung Seloka Health Center, Kotabaru District. The results show that 18 respondens (85.7%) who gave MP-ASI early to infants aged <6 months did not receive adequate family support. Statistical analysis reveals a significant relationship between family support and early complementary feeding (p-value = 0,000 < 0,005). Furthermore, all 15 respondents (100%) who gave MP-ASI early complementary feeding (p-value = 0,000 < 0.005). The conlusion: family support and maternal attitude significantly influence the early provision of complementary feeding to infants aged <6 months in the working area of the Tanjung Seloka Health Center, Kotabaru Distric. Strengthening family support and fostering positive maternal attitudes are essential to promoting exclusive breastfeeding practices.